Acarbose for Postprandial Hypotension With Glucose Metabolism Disorders: A Systematic Review and Meta-Analysis - Wang, Biqing; Zhao, Junnan; Zhan, Qiuxiao; Wang, Rongyanqi; Liu, Birong; Zhou, Yan; Xu, Fengqin (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: Postprandial hypotension is an independent predictive factor of all-cause mortality in older people. The drug management hasn’t achieved a satisfactory effect yet. In recent years, many studies have found that acarbose may be effective in the treatment of postprandial hypotension with glucose metabolism disorders. Objective: To assess the efficacy and safety of acarbose on postprandial hypotension with glucose metabolism disorders. Methods: PubMed (MEDLINE), Cochrane, EMBASE, Web Of Science, Clinical Trials, and relevant Chinese databases were searched from inception to 01 October 2020. The randomized controlled studies of acarbose in the treatment of postprandial hypotension with glucose metabolism disorders were included. Review Manager 5.3 software was used for quality evaluation and meta-analysis. Gradepro GDT software was used to GRADE the evidence for the research objectives. Results: A total of 4 randomized controlled studies including 202 participants were identified after screening. The meta-analysis showed that acarbose significantly attenuated the decrease in postprandial systolic blood pressure (MD: -9.84, 95% CI: -13.34 to -6.33), diastolic blood pressure (MD: -6.86, 95%CI: -12.89 to -0.83), and mean arterial pressure (MD: -8.10, 95%CI: -12.40 to -3.49) compared with the control group. One study reported a case of adverse reactions that included mild abdominal distension in the acarbose group (4.8%, 1/21). No adverse reactions were reported in the other three studies. Conclusion: Acarbose may attenuate the decrease in postprandial blood pressure and avoid the occurrence of postprandial hypotension in patients with postprandial hypotension and abnormal glucose metabolism disorders. More clinical trials are needed to make a clear conclusion.